ChemInform Abstract: Structure Revision of Caesalpinistas A and B and Isolation of a New Furanoditerpenoid from the Cotyledons of Caesalpinia decapetala var. japonica. Issue 27 (16th June 2016) - Kamikawa, Sayuri; Ohta, Emi; Nehira, Tatsuo; Omura, Hisashi; Ohta, Shinji
Abstract: The new diterpenoid, deoxycaesaljaponin A (I) is isolated along with the known caesalpinista B.